KEPEMIMPINAN KEPALA MADRASAH DALAM MENGELOLA SARANA DAN PRASARANA MA. HASYIM ASY'ARI JOGOROTO JOMBANG - Shofi‘i; Adibah Jauhari; Abdul Rouf (FAI- Undar, 2021)
A leader is required to have good character. and have the nature of siddiq, Amanah, Fathonah, impartial, all must be fair on the basis of the Qur'an and the Hadith of Rasulullah SAW..All leaders will be held accountable for what they lead, both leading themselves and others.In the Hadith of Rasulullah SAW. Mentionedلُّكُ مْ اع لُّكُ مْ لْ رَعِيَّتِهِْ(Each leader will be held accountable for what he leads)Madrasah Aliyah Hasyim Asy'ari Jogoroto Jombang is one of the top-level middle schools that has a lot of plus Islamic religious education taught to students.From several studies that have been carried out qualitatively at MA Hasyim Asy'ari Jogoroto Jombang with very minimal infrastructure but can carry out the teaching and learning process well, because the teaching and learning process activities are carried out in a simple way. By looking at the ability of the more important infrastructure facilities to be carried out, even though all of them are important.This research was formed by qualitative research with an approach to determine the ability of madrasas whose infrastructure classes are less fortunate.